Workers' guide to health and safety - Jailer, Todd; Lara-Meloy, Miriam; Robbins, Maggie (Berkeley, 2015)
"Work – how we spend most of our waking hours – has a huge effect on our health and our ability to care for ourselves, our families, and our communities. But in many factories around the world, workers face conditions that harm their health, endanger their lives, and keep them poor. This book provides tools to change that – to support workers' health promoters, union organizers, and employers in their efforts to create safer, healthier, fairer, and more fulfilling workplaces. The insights and techniques in the Workers' Guide to Health and Safety are useful in any factory, and especially in the garment, shoe, and electronics industries. Contents include: How to recognize workplace dangers caused by chemicals, machines, and more. Practical solutions to common workplace problems. How to be a workers' health promoter, and ideas for training. Activities and stories from workers and organizers. How to fight violence, gender discrimination, abuse of migrant workers, and low wages, which all affect workers' health. Work-related information on first aid, nutrition, mental health, family planning, and how to avoid HIV, TB, and other diseases. The book also includes an extensive chemical index presenting complex chemical information in a manner that is easy to understand that allows workers to identify chemicals they may be working with, understand their short?term and chronic health effects, and propose various ways to protect themselves by substituting safer chemicals, improving ventilation, and using the right personal protective equipment. Easy to use and full of illustrations, the Workers' Guide to Health and Safety demystifies occupational safety and health to make it relevant and accessible to everyone."